THE ROLE OF EMPLOYEE PERFORMANCE REGARDING THE EFFECT OF WORK DISCIPLINE AND LEADERSHIP - Willy Yusnandar; Jasman Saripuddin Hasibuan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of this research is toTo find out and analyze the effect of work discipline and work discipline on the performance of the employees of the Regional Water Company (PDAM) Tirtanadi HM Branch. Yamin Medan. The research approach carried out by the researcher is associative research. The number of samples in this study amounted to 33 respondents. The data collection technique uses primary data in the form of a questionnaire and uses a Likert scale in the selection of assessment responses, while the data analysis technique uses multiple linear analysis, classical assumptions, hypothesis testing, coefficient of determination. Based on the results of data analysis, the work discipline variable has a partial effect on employee performance. Furthermore, the work discipline variable has a partial effect on employee performance.